2016
DOI: 10.1093/ajh/hpw002
|View full text |Cite
|
Sign up to set email alerts
|

High Short-Term Blood Pressure Variability Predicts Long-Term Cardiovascular Mortality in Untreated Hypertensives But Not in Normotensives

Abstract: A high short-term BPV is significantly predictive of long-term cardiovascular mortality in untreated hypertensive but not normotensive community-based subjects, independently of office or 24-hour SBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 26 publications
1
53
0
2
Order By: Relevance
“…ARV exhibited the greatest reproducibility during both the observation and treatment periods. In agreement with those results, ARV was a significant predictor in 10 of the 11 studies with a minimum number of BP readings below the average lowest sampling rate …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…ARV exhibited the greatest reproducibility during both the observation and treatment periods. In agreement with those results, ARV was a significant predictor in 10 of the 11 studies with a minimum number of BP readings below the average lowest sampling rate …”
Section: Discussionsupporting
confidence: 88%
“…Hsu et al investigated the prognostic value of a high BPV in normotensive and hypertensive subjects over a median follow‐up of 20 years . The results showed that ARV predicted cardiovascular mortality independent of conventional risk factors plus office BP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies available showing better prognostic value of ARV in CV risk assessment compared to SD and SBP (16,23).…”
Section: Discussionmentioning
confidence: 99%